Gut microbiota assemblages of generalist predators are driven by local- and landscape-scale factors - Saqib, Hafiz Sohaib Ahmed; Sun, Linyang; Pozsgai, Gabor; Liang, Pingping; Goraya, Mohsan Ullah; Akutse, Komivi Senyo; You, Minsheng; Gurr, Geoff M.; You, Shijun (Frontiers in Microbiology, 2023)
The gut microbiomes of arthropods have significant impact on key physiological functions such as nutrition, reproduction, behavior, and health. Spiders are diverse and numerically dominant predators in crop fields where they are potentially important regulators of pests. Harnessing spiders to control agricultural pests is likely to be supported by an understanding of their gut microbiomes, and the environmental drivers shaping microbiome assemblages. This study aimed to deciphering the gut microbiome assembly of these invertebrate predators and elucidating potential implications of key environmental constraints in this process. Here, we used high-throughput sequencing to examine for the first time how the assemblages of bacteria in the gut of spiders are shaped by environmental variables. Local drivers of microbiome composition were globally-relevant input use system (organic production versus conventional practice), and crop identity (Chinese cabbage versus cauliflower). Landscape-scale factors, proportion of forest and grassland, compositional diversity, and habitat edge density, also strongly affected gut microbiota. Specific bacterial taxa were enriched in gut of spiders sampled from different settings and seasons. These findings provide a comprehensive insight into composition and plasticity of spider gut microbiota. Understanding the temporal responses of specific microbiota could lead to innovative strategies development for boosting biological control services of predators.